2022
DOI: 10.3390/biomed2010005
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Function and Neuropsychiatric Disorders after COVID-19: A Long Term Social and Clinical Problem?

Abstract: SARS-CoV-2 is one more virus that can affect the brain in one way or another. Now, we are only beginning to understand some mechanisms and the degree to which it can impact the nervous system. Considering the rapid accumulation of knowledge about multiple neurological and cognitive symptoms in COVID-19 patients, it seems useful to encourage the development of systematic approaches for the diagnosis, management and treatment of the cognitive aspects of COVID-19. From what is known at this time about the impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Brain RAS, SARS-CoV-2, and Cognitive Impairment. There are reports on the effect of COVID-19 on cognitive function [106]. Brain imaging techniques on participants infected with SARS-CoV-2 have revealed reductions in gray matter thickness in some areas of the cortex and white matter, which was accompanied by a cognitive decline [107,108].…”
Section: Brain Ras Sars-cov-2 and Oxidativementioning
confidence: 99%
“…Brain RAS, SARS-CoV-2, and Cognitive Impairment. There are reports on the effect of COVID-19 on cognitive function [106]. Brain imaging techniques on participants infected with SARS-CoV-2 have revealed reductions in gray matter thickness in some areas of the cortex and white matter, which was accompanied by a cognitive decline [107,108].…”
Section: Brain Ras Sars-cov-2 and Oxidativementioning
confidence: 99%
“…Furthermore, as if the above statistics were not disquieting enough, an exacerbated increase in cases of depressive and anxiety disorders is expected because of the COVID-19 pandemic. Different psychiatric and epidemiological studies have been warning social and economic circumstances faced during and after the pandemic might be leading to irreversible effects on the mental health of children, youth, and adults [6][7][8]. Furthermore, recent reports have suggested the potential impact of acute SARS-CoV-2 infection on the brain and central nervous system as a side effect of the hyperinflammatory cascade, which could lead to cognitive and neurological sequela in COVID-19 patients [7,9].…”
Section: Introductionmentioning
confidence: 99%
“…Different psychiatric and epidemiological studies have been warning social and economic circumstances faced during and after the pandemic might be leading to irreversible effects on the mental health of children, youth, and adults [6][7][8]. Furthermore, recent reports have suggested the potential impact of acute SARS-CoV-2 infection on the brain and central nervous system as a side effect of the hyperinflammatory cascade, which could lead to cognitive and neurological sequela in COVID-19 patients [7,9]. Preliminary evidence showed that about 23% of 40,000 patients presented neuropsychiatric symptoms, including anxiety, stress, and psychosis; however, more in-depth research is required to determine the tangible magnitude of neurological impacts in recovered COVID-19 patients [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation